Gendering the Tsunami : women's experiences from Sri Lanka - De Mel, Neloufer; Ruwanpura, Kanchana N. (Colombo : International Centre for Ethnic Studies, 2006)
Study with reference to Hikkaduwa and Betticaloa in Sri Lanka.
Keywords: Disaster victims -- Rehabilitation -- Sri Lanka -- Hikkaduwa; Disaster victims -- Rehabilitation -- Sri Lanka -- Batticaloa; Women -- Rehabilitation -- Sri Lanka -- Hikkaduwa; Women -- Rehabilitation -- Sri Lanka -- Batticaloa; Indian Ocean Tsunami, 2004.; Tsunamis -- Sri Lanka